Periodontal treatment approach for dihydropyridine induced gingival overgrowth with or without drug substitution - ÖZTÜRK ÖZENER, HAFİZE; KURU, LEYLA (My University, 2022)
Objectives: The aim of this study is to evaluate clinical effectiveness of nonsurgical periodontal treatment (NSPT) in patients with drug induced gingival overgrowth (DIGO) with or without drug substitution in comparison with patients presenting inflammatory gingival overgrowth (GO). Material and Methods: A total of 17 patients with generalized GO were included in this clinical trial. Based on the medical physicians consultation, DIGO patients who continued using dihydropyridine were allocated to the Group 1 (n=6), whereas patients whose drug substitution was carried out were allocated to the Group 2 (n=5). Group 3 (n=6) subjects had inflammatory GO. All study groups received NSPT for 4 sessions. At baseline and 6 weeks after NSPT, plaque index, gingival index, bleeding on probing (BOP), probing depth (PD) and, plaster model and photographic GO scores were measured. Results: NSPT resulted in significant decreases in periodontal clinical parameters in all groups (p<0.05). Intergroup comparisons of baseline measurements revealed no statistically significant differences (p>0.05) except PD value which was higher in the Group 1 compared to the Group 2 (p<0.05). Comparisons of post-NSPT data among groups exhibited statistically significant difference only between Groups 1 and 2 in the model and photographic GO scores (p<0.05). Conclusions: After the 6-week evaluation period, NSPT was found to be an effective method in reducing the severity of inflammation and size of overgrown gingival tissues in patients with DIGO and inflamatory GO. Substitution of drug causing GO provided further contribution to NSPT regarding the size of overgrown gingiva in the patients with DIGO.

Amaç: Bu çalışmanın amacı, ilaca bağlı dişeti büyümesi (İBDB) gösteren ve ilaç değişimi yapılan ve yapılmayan hastalarda cerrahi olmayan periodontal tedavinin (COPT) klinik etkinliğini değerlendirmek ve enflamatuvar dişeti büyümesi (EDB) gösteren hastalarla karşılaştırmaktır. Gereç ve Yöntemler: Ağızda generalize dişeti büyümesi görülen toplam 17 hasta araştırmaya dahil edildi. Dihidropiridine bağlı dişeti büyümesi olan hastalardan hekim konsültasyon sonucu ilacına devam edenler Grup 1 (n=6), ilaç değişimi yapılan hastalar ise Grup 2 (n=5) olarak ayrıldı. EDB görülen hastalar Grup 3’e (n=6) dahil edildi. Tüm çalışma gruplarına 4 seans COPT uygulandı. Başlangıçta ve COPT’den 6 hafta sonra plak indeks, gingival indeks, sondalamada kanama , sondalama derinliği (SD) ile alçı model ve fotoğrafik dişeti büyümesi skorları ölçüldü. Bulgular: Tüm hasta gruplarında COPT sonrası tüm klinik parametrelerde azalma gözlendi (p<0.05). Başlangıç ölçümlerinin gruplar arası karşılaştırmasında, Grup 1’de Grup 2’ye göre daha yüksek olan SD değeri (p<0.05) dışında anlamlı bir fark görülmedi (p>0.05). COPT sonrası verilerin gruplar arasında karşılaştırılmasında, yalnızca Grup 1 ve 2 arasında model ve fotoğrafik dişeti büyümesi değerlerinde istatistiksel olarak anlamlı fark bulundu (p<0.05). Sonuçlar: COPT’nin İBDB ve EDB görülen hastalarda 6 haftalık süreçte enflamasyonun şiddetinin ve büyümüş dişeti dokularının boyutlarının azaltmasında etkili bir yöntem olduğu sonucuna varıldı. Dişeti büyümesini indükleyen ilacın değişimi, İBDB hastalarında büyümüş dişetinin boyutlarının azaltılmasında COPT’ye ek katkıda bulunduğu belirlendi.
Dihidropridine bağlı dişeti büyümesinde farklı ilaç rejimlerinde periodontal tedavi yaklaşımı
Keywords: Diş eti aşırı büyümesi; hipertansiyon; antihipertansifler; kökü düzleştirme; ilaç ikamesi; Gingival overgrowth; hypertension; antihypertension agents; root planing; drug substitution